Modelling shape evolution and heat flow of spray-formed ring preforms - Mi, J; Shi, Z; Grant, P (2005)
A finite element model has been developed to simulate the coupled effects of deposit shape evolution and heat flow inside spray formed ring-shaped deposits. The shape model was developed using Matlab and included the features of. (1) atomiser scanning; (2) substrate movement relative to the atomiser; and (3) sticking efficiency. Atomiser scan and various substrate horizontal travel speeds were studied to optimise the ring shape in terms of useful materials suitable for downstream processing. The heat flow model was developed using the commercial finite element code Femlab. A data mapping technique was developed to transfer thermal data between different domains when the computational domains are subject to changing geometry and therefore the coupled effects of shape evolution and heat flow were addressed.Spray forming of ring deposits was performed on the large spray forming unit at Oxford University. In-situ temperature measurements were carried put for acquisition of boundary conditions and validation of the heat flow model. Heat flow modelling revealed that edge effects had a strong influence on the ring thermal history and the porosity distribution inside the deposits is closely related to the local solidification time.